GREEN SUKUK DALAM PERSPEKTIF MAQASHID SYARIAH SEBAGAI INSTRUMEN KEUANGAN BERKELANJUTAN - Nurlatifah; Muhammad Aldi Akbar; Muhammad Muallifurrahmi Arramidly (Yayasan Pendidikan Literasi Borneo, 2026)
This study aims to analyze Green Sukuk as a sustainable financial instrument from the perspective of maqashid al-shariah. Green Sukuk represents an innovation in Islamic finance that integrates sharia principles with sustainable development objectives, particularly in financing environmentally friendly projects. This research employs a qualitative approach using a library research method by examining relevant literature on Islamic finance and sustainability. The findings reveal that Green Sukuk is strongly aligned with the objectives of maqashid al-shariah, particularly in the protection of wealth (hifz al-mal), life (hifz al-nafs), progeny (hifz al-nasl), and the environment (hifz al-bi’ah). In addition, Green Sukuk contributes to sustainable development through the financing of renewable energy, green transportation, and sustainable natural resource management. However, its development still faces several challenges, including the lack of standardization, limited market capacity, and low levels of investor literacy. Therefore, Green Sukuk has significant potential as an Islamic financial instrument that not only complies with sharia principles but also promotes public welfare and environmental sustainability.